Educational psychology : constructing learning - McInerney, D.M. 1948- 4 0 (Dennis M.),16; McInerney, V.; 5 (Frenchs Forest, N.S.W. : Pearson Education Australia)
Setting the standard for educational psychology texts in Australia and New Zealand, this is the most comprehensive, authoritative and intellectually accessible coverage of educational psychology available. Includes completely updated content reflecting recent advances in the discipline.
Includes index.
Keywords: 2 -- 0; 6; Educational psychology; 20; 2